The Commercial Bottom Trawling Industry in Florida: Balancing Environmental Impact with Economic Contribution - Chuck Adams (EDIS)
This is EDIS document FE345, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published August 2002.